1994
DOI: 10.1002/1098-108x(199411)16:3<307::aid-eat2260160313>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Body size estimation and body dissatisfaction in eating disorder patients and normal controls

Abstract: In this study comparing 41 eating disorder patients and 34 female controls, the video distortion technique was used to test the accuracy of body size estimation and to assess the ideal body image. No difference was found in the estimation of actual body sizes, although the accuracy of estimation was quite variable in both bulimics and anorexics. With regard to the ideal body image,significant differences were found: All bulimics and 92.6% of the controls wished to be thinner versus 42.9% of the anorexics (23.8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 7 publications
2
15
0
1
Order By: Relevance
“…body size or not is still controversial. Whilst numerous studies have reported such overestimation (13,17,22,25,39), others have been unable to replicate these results (8,9,20). Probst at al.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…body size or not is still controversial. Whilst numerous studies have reported such overestimation (13,17,22,25,39), others have been unable to replicate these results (8,9,20). Probst at al.…”
Section: Discussionmentioning
confidence: 99%
“…Video distortion method (VDM), either on a TV monitor or on a life-size screen, has been the method most frequently used in the last few years (eight out of 13 studies, that is 61.5 %) (8,9,13,22,27,29,31,38).Video distortion was used mainly as a whole body technique, although Gardner et al introduced body region estimation in VDM as well (13).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,12 Empirical work assessing the specificity of body size overestimation for eating disorders has yielded inconsistent results. [13][14][15] These inconsistencies might be due to methodological factors, since body perception assessment varied from light beam apparatuses in earlier studies 16 to the application of distortable photographs in more recent works. 17 Using photographs, however, reduces investigations of the perception of one's own body to its static properties.…”
Section: Introductionmentioning
confidence: 99%
“…Bowden et al (1989) found the most substantial correlations between the affective response and the BDQ and the EDI subscales Body Dissatisfaction and Drive for Thinness. Fernandez, Probst, Meermann, and Vandereycken (1994) reported that BAT scores were negatively correlated with the desired body size in anorectic and bulimic patients as well as in control subjects. The results of both studies correspond with our findings.…”
Section: Discussionmentioning
confidence: 99%